Analysis of Consumers’ Impulsive Buying Behavior Under the Recommendation Model Empowered by Quantum Technology - Huang, Qifan (Innovative Applications of AI, 2026)
With the breakthrough development of quantum computing technology, quantum technology is based on the superposition and entanglement characteristics, and can effectively resolve the bottleneck of traditional recommendation model in processing high dimensional data, feature extraction efficiency and so on. Taking the recommendation model with the help of quantum technology as the research object, the impact of consumers’ impulsive buying behavior is investigated. Through the establishment of a controlled experiment to compare the difference in the score of experts on different aspects of consumers’ impulsive buying behavior under the quantum-empowered recommendation model and the traditional recommendation model, and to explore the influence path and intensity of quantum technology’s empowerment on consumers’ impulsive buying. The study finds that the recommendation model driven by quantum technology is much better than the ordinary model both in terms of accuracy of personal match and efficiency of information push. And also it will greatly improve the possibility of consumers making a sudden purchase, it can make people feel more emotionally charged and make the price of choosing more, it can also provide a basis for marketing to improve.